Spouse Burden in Patients with Alcohol Dependence Syndrome - Gautam, Sanjeev Chandra; Bhattarai, Yash (Nepal Journal of Neuroscience, 2019)
Use of alcohol has been one of the major source of recreation and stress relievers to date and it is one of the most abused substances in the world due to its free availability. The cost that a spouses incur in terms of economic hardships, social isolation and physical strain can be referred to as Spouse Burden. Spouses play an important role inpatient’s support and treatment and with a study like this there might be a better understanding of the problem. A descriptive, cross-Sectional hospital based study was done in 62 patients who met the diagnostic criteria for Alcohol Dependence Syndrome (ICD-10 DCR) and consents were taken from required personnel.Most of the patients examined were in the age group 40 to 60 years of age (72.6%) followed by the age group up to 40 (22.6%). 72.5% of the spouses were up to 40 years of age, followed by spouses of the age group 40-60 (27.5%).Males were the primary alcohol abusers(87%).51.6% of the patients were unemployed and the rest 48.4% was still employed whereas 51.6%of the spouses were employed and the rest48.4% unemployed. 51.6% of the patients were illiterate whereas majority of the spouses were literate(67.7%).There is a significant severity of burden of alcohol dependence syndrome in spouses and these verity of dependence is positively correlated with spouse burden. Financial, spouse routine, spouse interaction, physical and mental health of other members of the family were significantly affected with increase in dependence.